𝑞-Gaussian Distributions: Simplifications and Simulations - Paweł J. Szabłowski (Journal of Probability and Statistics)
We present some properties of measures (𝑞-Gaussian) that orthogonalize the set of 𝑞-Hermite polynomials. We also present an algorithm for simulating i.i.d. sequences of random variables having 𝑞-Gaussian distribution.